2013
DOI: 10.1111/sjop.12068
|View full text |Cite
|
Sign up to set email alerts
|

Investigating medical decision‐making capacity in patients with cognitive impairment using a protocol based on linguistic features

Abstract: A critical question is whether cognitively impaired patients have the competence for autonomous decisions regarding participation in clinical trials. The present study aimed to investigate medical decision-making capacity by use of a Swedish linguistic instrument for medical decision-making (LIMD) in hypothetical clinical trials in patients with Alzheimer's disease (AD) and mild cognitive impairment (MCI). Three comparable groups (age, education) participated in the study: AD (n = 20; MMSE: 24.1 ± 3.3) and MCI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 24 publications
0
28
0
2
Order By: Relevance
“…Linguistic instrument for medical decision‐making consists of three parts: (1) three vignettes; (2) a standardized interview; and (3) a standardized scoring protocol. As the test–retest reliability of LIMD has been shown to be very good ( R = 0.94, p < 0.001; Tallberg et al ., ), the present study refers to the LIMD score as a mean value between two evaluations made by the same experienced rater (IMT).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Linguistic instrument for medical decision‐making consists of three parts: (1) three vignettes; (2) a standardized interview; and (3) a standardized scoring protocol. As the test–retest reliability of LIMD has been shown to be very good ( R = 0.94, p < 0.001; Tallberg et al ., ), the present study refers to the LIMD score as a mean value between two evaluations made by the same experienced rater (IMT).…”
Section: Methodsmentioning
confidence: 99%
“…Each of the three LIMD criteria was defined, and each criterion received a score on a continuous scale, and the summed score was used as a measure of LIMD. The LIMD score is based on predefined linguistic features such as independence of the utterances, accuracy, inferences, and coherence for each established criterion (see Tallberg et al ., for more details).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, all patients with mild AD were impaired in understanding the treatment situation, a finding that is in line with other studies 7 and might be partially explained by linguistic difficulties. 8 Over a 2-year period, patients with mild AD showed a marked decline in appreciation, reasoning, and understanding. The authors suggested that reasoning and understanding might decline more precipitously over time than other domains; thus, changes in those abilities might be sensitive indicators of impairment in capacity to consent as the disease progresses.…”
Section: 3mentioning
confidence: 99%
“…Previous studies have shown that individuals with AD have limited medical decision‐making capacity (MDC) already in early stages of the disease (Huthwaite, Martin, Griffith, Anderson, Harrell & Marson, ; Marson, Ingram, Cody & Harrell, ; Marson, Schmitt, Ingram & Harrell, ; Okonkwo, Griffith, Belue et al ., ; Okonkwo, Griffith, Copeland et al ., ; Tallberg, Stormoen, Almkvist, Eriksdotter & Sundström, ). Problems arise regarding understanding, reasoning and appreciation (Marson, Cody, Ingram & Harell, ; Marson, Ingram et al ., ; Moye, Karel, Gurrera & Azar, ) as well as evaluating risks and benefits and expressing a decision (Tallberg et al ., ). Correlations have been found between MDC and other cognitive functions in AD, for example verbal retrieval (Gurrera, Moye et al ., ), verbal knowledge, episodic memory, cognitive speed and working memory (Stormoen, Almkvist, Eriksdotter, Sundstrom & Tallberg, ).…”
Section: Introductionmentioning
confidence: 99%